Autoantibodies Against Lysosome Associated Membrane Protein-2 (LAMP-2) in Pediatric Chronic Primary Systemic Vasculitis - Gibson, Kristen M.; Kain, Renate; Luqmani, Raashid A.; Ross, Colin J.; Cabral, David A.; Brown, Kelly L. (Frontiers in Immunology, 2021)
Background: ANCA-associated vasculitis (AAV) is a small vessel vasculitis in adults and children that commonly affects the kidneys. Although the frequent antigenic, and presumed pathogenic, targets of ANCA in AAV are PR3 and MPO, ANCA against lysosome associated membrane protein-2 (LAMP-2), a lesser known ANCA antigen that is expressed on the glomerular endothelium, are present in some adults with AAV-associated renal disease. LAMP-2-ANCA has not been assessed in children with chronic systemic vasculitis, and, if present, would be a potentially valuable biomarker given that treatment decisions for these pediatric patients at diagnosis are largely informed by kidney function. Methods: A custom ELISA, using commercially available reagents, was designed to detect autoantibodies to human LAMP-2 in serum. Sera obtained from 51 pediatric patients at the time of diagnosis of chronic primary systemic vasculitis (predominantly AAV) was screened. LAMP-2-ANCA titres were evaluated for correlation with clinical metrics of disease activity, MPO- and PR3-ANCA titres, and renal function. Results: LAMP-2-ANCA (>1000 ng/mL) were detected in 35% (n = 18) of pediatric systemic vasculitis patients, with high positive titres (>1500 ng/mL) detected in 20% (n = 10). Titres below <1000 ng/mL were considered low with unknown clinical relevance. Although LAMP-2-ANCA titres did not significantly differ between patients with AAV versus ANCA-negative vasculitis, only AAV patients had high concentrations (>1500 ng/mL) of LAMP-2-ANCA. LAMP-2-ANCA titres did not correlate with measures of disease activity at the time of diagnosis. In contrast, for patients with 12-month post diagnosis follow-up, a negative correlation was observed between the change in GFR at 12-months and LAMP-2-ANCA titre at diagnosis. Conclusions: LAMP-2-ANCA are prevalent in children with chronic systemic vasculitis affecting small-to-medium vessels. Although the highest concentrations of LAMP-2-ANCA were observed in individuals positive for classic ANCA (MPO- or PR3-ANCA), similar to previous reports on adult patients, LAMP-2-ANCA titres do not correlate with classic ANCA titres or with overall disease activity at diagnosis. Renal disease is a common manifestation in systemic small-medium vessel vasculitis (both in adults and children, though more severe in children) and our preliminary data suggest LAMP-2-ANCA at diagnosis may be a risk factor for worsening renal disease.